X-ray and ultrasound semiotics of mucinous carcinoma of the breast - K. A. Lesko; A. B. Abduraimov (ABV-press, 2014)
The article describes the main epidemiological, clinical and morphological diagnostic features of one of the rare breast cancer form - mucinous carcinoma of the breast. Current scientific data are followed by the results of own research the 9-year period of research.Authors draw attention to the very complex radiology peculiarities of the mucinous carcinoma of the breast.